Seaborne trade between South Asia and Southeast Asia - David Wignall; Mark Wignall (Asian Development Bank Institute (ADBI), 2014)
This paper examines the seaports responsible for handling the majority of trade around the Bay of Bengal and identifiesthe projects that will enable trade and contribute to improving maritime infrastructure. It reviews the nature, potential evolution,and primary types of maritime trade around the bay, and analyzes the ships carrying that trade. It also reviews the potential changes that would have a significant impact on trade patterns, with special consideration of the Indian East Coast Corridor study. The paper likewise examines the main ports on the Bay of Bengal to understand their history, regulatory regimes, purpose, capabilities, primary specifications, constraints, productivity, fitness for purpose when compared to other ports in comparable situations, and their opportunities to improve and develop. Finally, the paper develops strategic options through which the seaports around the baycan adjust and develop to support the evolution of trade. The paper provides policy recommendations on how constraints can be addressed.
Keywords: F14; L91; 330; bay of bengal; maritime trade and transport; port infrastructure and development; container ports